Efektivitas Implementasi Kebijakan Pengendalian Pencemaran Udara di Indonesia - Gefira Minhatul Maula (Savana, 2024)
Air pollution is a significant environmental problem in Indonesia, affecting public health and environmental quality. Air pollution control policies have been implemented to address this issue. This study aims to evaluate the effectiveness of the implementation of air pollution control policies in Indonesia from an environmental law perspective and examine community participation in supporting the implementation of these policies. This study uses a juridical-normative method with a case study approach, namely Decision Number: 14 / PDT.G / LH / 2018 / PN.Gns. The results of the study are that this decision is a dispute between residents of Untoro Village, Trimurjo District, Central Lampung Regency and PD. Subur Jaya which is located in Untoro Village, Trimurjo District, Central Lampung Regency. This dispute occurred because of the pollution of PD. Subur Jaya rice factory waste which has disturbed local residents and caused air pollution. Analysis of the decision shows that although the air pollution control policy has been well formulated, its implementation faces various obstacles, such as lack of coordination between institutions, limited resources, and ineffective law enforcement. In addition, public participation in supporting this policy is still low, due to the lack of socialization and education regarding the importance of air pollution control. In conclusion, the implementation of air pollution control policies in Indonesia has not been fully effective from an environmental law perspective. Improved coordination between institutions, strengthened law enforcement, and increased public participation through more intensive socialization and education are needed to achieve better results in air pollution control in Indonesia.